P-184 Delivering an integrated end of life care service – is it sustainable six years on?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Heaps, Kate; McCarthy, Alison; Devlin, Jonathan
Abstract : Background: The Greenwich Care Partnership (GCP) was born out of the Marie Curie Delivering Choice Programme (DCP). Three service providers developed the service, with the hospice as prime contractor and two sub-contracted partners. The service has been in operation since 2011. Service Aims: To increase the number of people who are able to die in their place of choice To ensure appropriate health and personal care services To provide family support. Service Approach: The service operates alongside core services to support high quality care across four areas: Care co-ordination Rapid Response Service – Out of Hours Personal care and support Night care. Elements are provided by different providers working together to ensure seamless care 24/7. The following data will be reported: Activity data collected over the duration of the project HR information regarding staff retention and staff satisfaction ratings VOICES feedback. Service outcomes: Sustained increase in home and hospice deaths Maintained reduction in hospital admissions, length of stay and deaths Low staff turnover and high job satisfaction for carers in service Catalysing further integration and service innovation High patient and carer satisfaction. Challenges: 'Flat' funding with growth in service activity Organisational change at CCG and continuity of communication with partner organisations Continued lack of GP engagement in end of life care. Conclusion: The service continues to deliver its intended outcomes and has acted as a catalyst for further innovation and integration. Despite a number of challenges throughout the project, the service remains sustainable and is a key part of the hospice service.